Pathophysiology of tumor progression and possibilities of using polarization biomedical optics methods in the diagnosis of papillary thyroid cancer - Yu.Ye. Rohovyi; O.V. Bilookyi; O.H. Ushenko; V.V. Bilookyi (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. Clinical diagnosis of papillary thyroid cancer usually occurs at the stage of tumor progression accompanied by intensive processes of growth, invasion, formation of blood vessels to provide blood supply to the tumor, the structure and quantitative changes of which can be more informatively accurately assessed by polarization biomedical optics. The purpose of the study was to substantiate the possibility of using polarization biomedical optics methods in the diagnosis of papillary thyroid cancer based on the principles of comprehensiveness and integrated pathophysiology. Materials and methods. Two groups of patients were studied: the control group — healthy donors (n = 51), the experimental group — patients with papillary thyroid cancer (n = 51) who underwent a puncture biopsy of the thyroid gland for diagnostic purposes using the fundamental idea of polarization biomedical optics with two analytical approaches — statistical and topographic (multifractal). Instrumental laser methods were used: polarization, interference, digital holographic. The statistical parameters of polarization azimuth maps, polarization azimuth of phase and multifractal spectra of digital microscopic images of native histological sections of thyroid biopsy from patients with papillary cancer were quantitatively evaluated with the determination of average, dispersion, asymmetry and excess. The significance of differences compared to the control, taken as 100 % was assessed using the Student’s parametric test (p < 0.05). Results. A significant increase in the asymmetry and excess of the polarization azimuth, a significant inhibition of the average polarization azimuth of phase digital microscopic images of native histological sections of thyroid biopsy from patients with papillary cancer, a significant increase in the asymmetry and excess of phase digital microscopic images of native histological sections of thyroid biopsy from patients with papillary cancer were revealed. A significant increase in dispersion and a probable decrease in the asymmetry and excess of multifractal spectra of polarization azimuth maps of digital microscopic images of native histological sections of thyroid biopsy in patients with papillary cancer were shown. Conclusions. A significant increase in the biophysical optical parameters of digital microscopic images of native histological sections of thyroid biopsy of patients with papillary cancer was found due to increased growth of connective tissue around transformed T thyrocytes and blood vessels to provide their nutrition. A probable inhibition of the average azimuth of polarization of phase digital microscopic images of native histological sections of thyroid biopsy of patients with papillary cancer and a probable decrease in the asymmetry and excess of multifractal spectra of polarization azimuth maps of digital microscopic images of native histological sections of thyroid biopsy of patients with papillary cancer are caused by papillary proliferation of transformed T thyrocytes as an amorphous component in patients with papillary cancer as a result of activation of tumor progression with intensive processes of growth, invasion, and formation of blood vessels to provide blood supply to the tumor.